If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -36 + 9 = 0 Reorder the terms: -36 + 9 + 3y = 0 Combine like terms: -36 + 9 = -27 -27 + 3y = 0 Solving -27 + 3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 3y = 0 + 27 Combine like terms: -27 + 27 = 0 0 + 3y = 0 + 27 3y = 0 + 27 Combine like terms: 0 + 27 = 27 3y = 27 Divide each side by '3'. y = 9 Simplifying y = 9
| 2(3d-1)=d+58 | | 13x^2y^4-26xy=0 | | x^2-8x^1/2=0 | | 5/2+7/8=x | | 2a(a+1)-3(a+1)=0 | | 5x-5/(x-1)(x-1) | | -4x+1=-9 | | 1m=9 | | 5/2+7/8 | | 13+3/4x=28 | | 64-4j=j+9 | | -17x^2+51x=0 | | (5x-5)/(x-1)(x-1) | | 64-4j=j+10 | | -19=m-28 | | 4.2=0.8k | | x(21x+13)+2=0 | | K^2=5k-6 | | 60/6+38= | | 2(x+-1)=12 | | 6m+25=9m-2 | | 7(2x-4)=-196 | | -5+5+10= | | 5m=70 | | 5b-15=2b+15 | | 3x-2+3x=40 | | 8x+-8=6x+7 | | c/0.2=-1.6 | | -1/2z=3/4-1/4 | | 5x+17-4x=-8-13 | | -109+9x=164-12x | | (u+1/2)-(u-1/49)=1 |